Circulating MicroRNAs as Biomarkers of Accelerated Sarcopenia in Chronic Heart Failure. Issue 1 (30th August 2021) - Qaisar, Rizwan; Karim, Asima; Muhammad, Tahir; Shah, Islam; Khan, Javaidullah
Background: Sarcopenia is a critical finding in patients with chronic heart failure (CHF). However, the search for a definitive biomarker to predict muscle and functional decline in CHF remains elusive. Objectives: We aimed to correlate the circulating levels of selected miRs with the indexes of sarcopenia during healthy aging and in patients with CHF. Methods: We analyzed the association of circulating microRNAs (miRs) levels including miR-21, miR-434-3p, miR424-5p, miR-133a, miR-455-3p and miR-181a with sarcopenia indexes in male, 61–73 years old healthy controls and patients with CHF (N = 89–92/group). Results: Patients with CHF had lower hand-grip strength (HGS), appendicular skeletal mass index (ASMI) and physical capacity than healthy controls. Circulating miR-21 levels were higher and miR-181a, miR-133a, miR-434-3p and miR-455-3p levels were lower in patients with CHF than healthy controls. Among the sarcopenia indexes, HGS showed the strongest correlation with miR-133a while ASMI showed the strongest correlations with miR-133a, miR-434-3p and miR-455-3p. Among the miRs, miR-434-3p showed the highest area under the curve in testing for sensitivity and specificity for CHF. These changes were associated with higher expressions of the markers of inflammation, oxidative stress and muscle damage in CHF patients. Conclusion: Taken together, our data show that circulating miRs can be useful markers of muscle health and physical capacity in the sarcopenic elderly with CHF.